A NbO type Cu(ii) metal–organic framework showing efficient catalytic activity in the Friedländer and Henry reactions. Issue 24 (7th June 2017) - Gupta, Anoop K.; De, Dinesh; Bharadwaj, Parimal K.
Abstract : A three-dimensionalNbO type Cu(ii )-MOF1 shows excellent and efficient heterogeneous catalytic activity for the Friedländer reaction and Henry reaction. Abstract : A three-dimensionalNbO type porous metal–organic framework1 containing both tertiary amine groups and paddle wheel dinuclear Cu2 (COO)4 secondary building units as the active centre was synthesized at room temperature. The activated framework1′ can be used as an efficient heterogeneous catalyst for the synthesis of quinoline derivatives by the Friedländer reaction and for the synthesis of β-nitroalcohols by the Henry (nitroaldol) reaction. This MOF-based heterogeneous catalyst is easily recycled and reused further without losing its structural integrity and catalytic activity.